Volume 2C: Turbomachinery 2018
DOI: 10.1115/gt2018-75733
|View full text |Cite
|
Sign up to set email alerts
|

High Fidelity Spectral/hp Element Methods for Turbomachinery

Abstract: The high order spectral/hp element methods implemented in the software framework Nektar++ are investigated for scale-resolving simulations of LPT profiles. There is a growing demand for high fidelity methods for turbomachinery to move towards numerical “experiments”. The study contributes at building best practices for the use of emerging high fidelity spectral element methods in turbomachinery predictions, with focus on the numerical details that are specific of these classes of methods. For this reason, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…See Ref. [40] for more details about the dimensionless geometrical parameters of T106 LPT blade. The numerical investigations of the T106A turbine were performed at moderate Reynolds number (𝑅𝑒 = ) of 51,800.…”
Section: Physical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Ref. [40] for more details about the dimensionless geometrical parameters of T106 LPT blade. The numerical investigations of the T106A turbine were performed at moderate Reynolds number (𝑅𝑒 = ) of 51,800.…”
Section: Physical Descriptionmentioning
confidence: 99%
“…Besides, as discussed by Cassinelli et al [40] using 96 Fourier planes in span direction provides an appropriate degree of freedom (DOF) and it highly accurate to capture the details of flow unsteadiness over LPT blades. Therefore, Nz=96 is selected in the span direction for further simulations.…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Garai et al [30] performed DNS of a linear T106D cascade and reported that the method was able to capture the main features of the flow, and attributed subtle differences between DNS and the reference data to the fact that freestream turbulence was not included in the simulation. In the DNS of the T106A cascade by Cassinelli et al [9], again no inflow turbulence or wakes were included. The effect of the polynomial order used, the spanwise domain size and the spanwise resolution were investigated and results were compared with experimental data up to exit Reynolds number 160,000, showing excellent agreement.…”
Section: Low-pressure Turbinementioning
confidence: 99%
“…3. Note, the purple line shows the exciting potential of high-order methods and hence the re-emergence of interest in such approaches in many applications including turbomachinery [8][9][10][11][12]. Flow Classification.…”
Section: Introductionmentioning
confidence: 99%